Functional somatic symptoms and their predictors in patients with major depressive disorder and fibromyalgia syndrome - YANARTAŞ, ÖMER; SAYAR, MUSTAFA KEMAL (My University, 2022)
© 2022 by Turkish Association of Neuropsychiatry.Introduction: Despite being different medical conditions, functional somatic symptoms (FSSs) are common in patients with major depressive disorder (MDD) and fibromyalgia syndrome (FMS). Higher levels of depression, anxiety, somatosensory amplification, hypochondriacal worry and alexithymia may be related to the severity of somatization in patients with MDD and FMS. We aimed to investigate the typology and severity of FSSs and the association between FSSs and these psychiatric symptoms in patients with MDD and FMS. Method: 56 MDD, 33 FMS, 21 CoMF (Comorbidity of MDD and FMS) patients, and 50 healthy participants were included in the study, respectively. Diagnosis of MDD and FMS was established according to DSM-IV-TR (Diagnostic and Statistical Manual of Mental Disorders, Revised Text), and ACR (American College of Rheumatology) 2010 diagnostic criteria. All participants were evaluated with self-report questionnaires including Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Somatosensory Amplification Scale (SSAS), Toronto Alexithymia Scale-20 (TAS-20), Whiteley Index-7 (WI-7), The Symptom Checklist-90-R (SCL-90-R) somatization subscale and Bradford Somatic Inventory-44 (BSI-44). Results: The severity of somatization was statistically significantly highest in the CoMF group, and similar in the FMS and MDD groups, and lowest in the control group according to the BSI-44 and SCL-90-R results. The typology of FSSs was quite similar in patients with MDD and FMS, and weakness, tiredness and neck pain were the most common FSSs in both groups. Independent predictors of FSSs were age, the severity of anxiety and alexithymia in the MDD group, however, it was only the severity of anxiety in the FMS group. Conclusions: Our results show that the typology and severity of FSSs are similar in MDD and FMS patients. Moreover, somatization appears to be more associated with anxiety in patients with MDD and FMS.
Major Depresif Bozukluk ve Fibromiyalji Sendromu Hastalarında İşlevsel Bedensel Belirtiler ve Belirleyicileri
Keywords: Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Psikiyatri; Sinirbilim ve Davranış; SİNİR BİLİMİ; Clinical Medicine (MED); Life Sciences (LIFE); PSYCHIATRY; NEUROSCIENCE & BEHAVIOR; NEUROSCIENCES; Genel Sinirbilim; Psikiyatri ve Ruh Sağlığı; General Neuroscience; Psychiatry and Mental Health; Alexithymia; anxiety; depression; fibromyalgia; hypochondriasis; somatization